Mapping of QTLs associated with recovery resistance to streak virus disease in maize - Ladejobi, O.; Salaudeen, M.T.; Kumar, P. Lava; Menkir, A.; Adesoye, A.; Atiri, G.; Gedil, Melaku A (Elsevier, 2018)
Maize streak virus (MSV, genus Mastrevirus, family Geminiviridae), vectored by the leafhoppers (Cicadulina sp.), is the most economically important viral disease of maize endemic to Sub-Saharan Africa and its offshore islands. Yield losses due to MSV are mainly controlled through use of resistant varieties. ‘Recovery’ (ability of plants to reduce symptom severity), is one of the types of resistance being used to develop MSV resistant cultivars through breeding. This study was conducted to map Quantitative Trait Loci (QTLs) associated with recovery resistance to MSV in a mapping population comprising 250 S1 lines derived from a cross between two MSV resistant lines. The population was genotyped using single nucleotide polymorphism (SNP) markers at 269 loci. A genetic map of 11 linkage groups was constructed comprising 230 SNP markers. Four QTLs, two putative QTLs with significant effect on chromosome 3 and two other QTLs with reduced effect on chromosomes 7 and 9, were identified from the population. The two QTLs on chromosome 3 together accounted for 47 to 51% of the total phenotypic variance while the other two QTLs accounted for 28 to 32% of the total variation. These QTLs originated from the two parents of the mapping population had both additive and dominance effects but interaction among the four loci was not significant. Further validation of these QTLs associated with recovery resistance in other diverse populations will lead to the development of new genomic resources to enhance breeding for MSV resistant maize.